Power equipment engine technology - Abdo, Edward (Delmar/Cengage Learning, 2011)
From the Back Cover: Power Equipment Engine Technology (PEET) is a comprehensive textbook that is designed to meet the basic needs of readers interested in the subject of small engine repair, and to help students become more qualified candidates for shops looking for well-prepared, entry-level technicians. PEET contains 17 chapters, beginning with a brief history of the internal combustion engine and ending with a chapter on troubleshooting various conditions found on any power equipment engine. Also, both two-stroke and four-stroke engines are covered. This book has been written to make the learning experience enjoyable, with easy-to-read-and-understand chapters and over 600 illustrations to assist visual learners with content comprehension. PEET can be used not only by pre-entry-level technicians but also as a reference manual by practicing technicians, and it will be helpful for the general consumer of power equipment engines that has an interest in understanding how they work. Power equipment technicians are currently sought after and will continue to be in demand in the future as technology advances in the manufacturing of modern power equipment engines.
Includes index.
Keywords: Internal combustion engines.; Internal combustion engines -- Maintenance and repair.; elektronické knihy; electronic books